Non‐metabolic function of MTHFD2 activates CDK2 in bladder cancer. Issue 12 (24th October 2021) - Liu, Xi; Liu, Shuangjie; Piao, Chiyuan; Zhang, Zhe; Zhang, Xiaotong; Jiang, Yuanjun; Kong, Chuize
Abstract: Bladder cancer is a common tumor with a high recurrence rate and high fatality rate, and its mechanism of occurrence and development remains unclear. Many proteins and metabolites reprogram at different stages of tumor development to support tumor cell growth. The moonlighting effect happens when a protein performs multiple functions simultaneously in a cell. In this study, we identified a metabolic protein, MTHFD2, which participates in the cell cycle by binding to CDK2 in bladder cancer. MTHFD2 has been shown to affect bladder cancer cell growth, which is independent of its metabolic function. We found that MTHFD2 was involved in cell cycle regulation and could encourage cell cycle progression by activating CDK2 and sequentially affecting E2F1 activation. In addition, moonlighting MTHFD2 might be regulated by the dynamics of the mitochondria. In conclusion, MTHFD2 localizes in the nucleus to perform a distinct function of catalyzing metabolic reactions. Moreover, the nuclear MTHFD2 activates CDK2 and promotes bladder cancer cell growth by modulating the cell cycle. Abstract : This study showed that MTHFD2's expression is correlated with poor prognosis in bladder cancer. Moreover, it could precipitate with CDK2 in a metabolic manner and activate E2F1 through CDK2 to induce rapid cell growth. Furthermore, MTHFD2 could be transcriptionally regulated by the CDK2‐E2F1 axis and translocated into the nucleus at the G1‐S phase associated with mitochondrial fusion. These results suggest that MTHFD2 participates in the cell cycle using a non‐metabolic function, which should be considered in the development of related therapeutics.